2016
DOI: 10.1093/hmg/ddw313
|View full text |Cite
|
Sign up to set email alerts
|

The humanRHOXgene cluster: target genes and functional analysis of gene variants in infertile men

Abstract: The X-linked reproductive homeobox (RHOX) gene cluster encodes transcription factors preferentially expressed in reproductive tissues. This gene cluster has important roles in male fertility based on phenotypic defects of Rhox-mutant mice and the finding that aberrant RHOX promoter methylation is strongly associated with abnormal human sperm parameters. However, little is known about the molecular mechanism of RHOX function in humans. Using gene expression profiling, we identified genes regulated by members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…We found that the human RHOXF1 motif (Figure 2b) is likely not utilized by Rhox proteins in mice even though more than 30 Rhox genes exist. Evidently, throughout multiple duplications, Rhox genes seem to have obtained other functionalities in mouse 38 in comparison to the two human RHOX genes that are expressed in reproductive tissues 39 . Therefore, although we found the human RHOXF1 motif to be highly active in mice, this motif is most likely utilized by other proteins such as the mouse specific Obox proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the human RHOXF1 motif (Figure 2b) is likely not utilized by Rhox proteins in mice even though more than 30 Rhox genes exist. Evidently, throughout multiple duplications, Rhox genes seem to have obtained other functionalities in mouse 38 in comparison to the two human RHOX genes that are expressed in reproductive tissues 39 . Therefore, although we found the human RHOXF1 motif to be highly active in mice, this motif is most likely utilized by other proteins such as the mouse specific Obox proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, based on these observations the gene remains an important candidate gene for human male infertility. Similar discrepancies in originally published allele frequencies and currently available allele frequencies were found in several other genes including NLRP14 (http://gnomad.broadinstitute.org/variant/11-7060977-A-T) (Westerveld et al 2006), SEPT12 (http://gnomad.broadinstitute.org/variant/16-4833970-C-T) (Lin et al 2012) and RHOXF1 (http://gnomad.broadinstitute.org/variant/X-119243190-C-T) (Borgmann et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in RHOXF1 and RHOXF2/2B found in patients with severe oligozoospermia stress the importance of these genes in male infertility (14,15). It has been shown that RHOXF2/2B mutations significantly impair the ability to regulate downstream genes such as transcription factors and chaperons from the HSP70 family (15).…”
Section: Rhoxmentioning
confidence: 99%
“…NR5A1 (6,7,8,9) and DMRT1 (10,11) are examples of autosomal genes in which heterozygous mutations are causative. However, sex-chromosomal genes are prime candidates because of their hemizygous state in males and TEX11 (12,13) and RHOX (14,15) are recent examples which, if mutated, cause male infertility.…”
Section: Introductionmentioning
confidence: 99%